2020
DOI: 10.3389/fnut.2020.00159
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation and Dietary Control of Triple Negative Breast Cancer

Abstract: Triple negative breast cancer (TNBC) represents a highly heterogeneous group of breast cancers, lacking expression of the estrogen (ER) and progesterone (PR) receptors, and human epidermal growth factor receptor 2 (HER2). TNBC are characterized by a high level of mutation and metastasis, poor clinical outcomes and overall survival. Here, we review the epigenetic mechanisms of regulation involved in cell pathways disrupted in TNBC, with particular emphasis on dietary food components that may be exploited for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…Song et al [ 344 ] demonstrated the anti-angiogenic effect of CAPE in a chick embryo chorioallantoic membrane (CAM) assay system. CAPE also suppressed VEGF secretion by MDA-MB-231 cells and the development of capillary-like tubes by endothelial cells, further indicating its anti-angiogenic potential [ 345 , 346 , 347 , 348 ]. Similarly, Izuta et al [ 347 ] reported that CAPE inhibits VEGF expression in human umbilical vein endothelial cells (HUVECs).…”
Section: Antitumor Activity Of Propolis and Its Polyphenolic/flavonoi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al [ 344 ] demonstrated the anti-angiogenic effect of CAPE in a chick embryo chorioallantoic membrane (CAM) assay system. CAPE also suppressed VEGF secretion by MDA-MB-231 cells and the development of capillary-like tubes by endothelial cells, further indicating its anti-angiogenic potential [ 345 , 346 , 347 , 348 ]. Similarly, Izuta et al [ 347 ] reported that CAPE inhibits VEGF expression in human umbilical vein endothelial cells (HUVECs).…”
Section: Antitumor Activity Of Propolis and Its Polyphenolic/flavonoi...mentioning
confidence: 99%
“…In addition, P10.EE reduced total biomass and proliferation of human brain-microvascular endothelial cells and reduced vessel sprouting in the CAM assay. The effects of Chinese red propolis and its related products on VEGF-induced proliferation and migration of HUVECs were also investigated [ 345 , 346 , 347 , 348 ]. Chinese red propolis inhibited both VEGF-induced HUVEC proliferation and migration.…”
Section: Antitumor Activity Of Propolis and Its Polyphenolic/flavonoi...mentioning
confidence: 99%
“…ERα is both a prognostic and predictive marker in BC, and hypermethylation of its promoter is a crucial gene‐silencing mechanism in ERα‐negative BC 32 . In ERα‐positive BC cell lines, such as MCF‐7, T47D, and ZR75‐1, the ESR1 promoter is considered nonmethylated 8,33 .…”
Section: Discussionmentioning
confidence: 99%
“…ERα is both a prognostic and predictive marker in BC, and hypermethylation of its promoter is a crucial gene‐silencing mechanism in ERα‐negative BC. 32 In ERα‐positive BC cell lines, such as MCF‐7, T47D, and ZR75‐1, the ESR1 promoter is considered nonmethylated. 8 , 33 Previously, a few EMT‐related transcriptional factors, such as Twist and ZEB1, were reported to induce hypermethylation of the ESR1 promoter and result in transcriptional repression of ERα.…”
Section: Discussionmentioning
confidence: 99%
“…MDA-MB-231 (ER-, PR-, and HER2-) cells express a higher Ki-67 expression contrary to MCF-F7 (ER+, PR+, and HER2-) cells and have been shown to have no p21 induction [ 112 ]. Employment of stilbenes like resveratrol to repress Ki-67 transcription might also be challenging because studies show that it prevents DNMT1 and MBD2 binding at the promoter of important oncogenes like BRCA1, thereby activating them [ 114 ]. The potential to make resveratrol work differentially, gene-to-gene, needs further research.…”
Section: Epigenetic Effect Of Stilbene On Genes and Proteins Related To Cell-proliferation And Metastasismentioning
confidence: 99%